4-Allyl-6-bromo-2-phenyl-4H-imidazo[4,5-b]pyridine monohydrate - Ouzidan, Y.; Rodi, Y.K.; Zouihri, H.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
In the molecule of the title compound, C(15)H(12)BrN(3)center dot H(2)O, the phenyl ring is coplanar with the imidazopyridine ring system [dihedral angle = 0.4 (1)degrees]. The water molecule is disordered over two positions with occupancies of 0.58 (1) and 0.42 (1), and it is linked to the main molecule via an O-H...N hydrogen bond.